2008
DOI: 10.1016/j.ajog.2007.05.038
|View full text |Cite
|
Sign up to set email alerts
|

The impact of race as a risk factor for symptom severity and age at diagnosis of uterine leiomyomata among affected sisters

Abstract: Self-reported race is a significant factor in the severity of UL among women with a family history of UL. Differences in disease presentation between races likely reflect underlying genetic heterogeneity. The affected sister-pair study design can address both epidemiological and genetic hypotheses about UL.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
57
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(61 citation statements)
references
References 19 publications
3
57
0
1
Order By: Relevance
“…For example, the incidence of hysteromyoma in African females is three times as high as that in Caucasian females (13). Also, compared with other ethnicities, African females with hysteromyoma are younger and have larger lesions, with hysteromyomas that grow faster (12,15). The incidence of hysteromyoma in females of African descent is higher than in individuals of other ethnicities, including Hispanic and Asian individuals (11,15,16).…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…For example, the incidence of hysteromyoma in African females is three times as high as that in Caucasian females (13). Also, compared with other ethnicities, African females with hysteromyoma are younger and have larger lesions, with hysteromyomas that grow faster (12,15). The incidence of hysteromyoma in females of African descent is higher than in individuals of other ethnicities, including Hispanic and Asian individuals (11,15,16).…”
Section: Discussionmentioning
confidence: 95%
“…Certain studies have shown that the incidence of hysteromyoma varies among populations of different ethnicities (11)(12)(13)(14)(15)(16). For example, the incidence of hysteromyoma in African females is three times as high as that in Caucasian females (13).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the United States, uterine leiomyomas occur two to nine times more often in black than in white women of all ages, and are associated with more serious symptoms in blacks, who are diagnosed at younger ages and have higher hysterectomy rates than whites 5,6,7,8,9,10,11 . The underlying mechanisms of this color/race inequality remain unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Epidemiological data on risk factors for the development of UL primarily originate from studies conducted in the United States. In these studies, higher frequencies of tumors stood out among black women 4,[23][24][25][26] , those exposed to factors associated with the increase in ovarian hormones (estrogen and progesterone), those undergoing hormonal therapy 27 , those consuming greater amounts of red meat and sausages 28 , those aged between 40 and 50 years 4,29 , those who had had an early menarche [30][31][32] , those with a high BMI 31,[33][34][35][36] and fat percentage 37 , and those with an increase in weight during adulthood 33,34,38 . On the other hand, lower frequencies of tumors were found in women who practiced physical activities 39 , smokers 30,33,40,41 , those with a higher number of children [30][31]36,42 , those who had reached menopause 36 and those who consumed greater amounts of fruits, vegetables and fish 28,35 .…”
Section: Introductionmentioning
confidence: 99%